BODY IMAGE EVALUATIONS OF ADOLESCENTS. (Fiep Bulletin - online, 2015)
Children and adolescents are more and more vulnerable to weight disturbances such as obesity and low weight. Thus, this work had as objective to evaluate the form that adolescents from public and private High Schools self-evaluated their body image with aid of silhouette illustrations. The sample was composed by 20% of the 14 to 17 years old students from public (131 students) and private (77 students) schools of Loanda/PR, totalizing 208 adolescents. It was used a questionnaire with body image silhouettes in which the adolescent indicated that one which more identified with herself or himself. The weight and stature, for the calculation of BMI, were collected during the Physical Education classes and the nutritional status was evaluated in agreement with NCHS/CDC (2000). The results indicated that although all the students were classified as euthrophic, in the public schools 76,19% of the male and 81,94% of the female self-evaluated themselves with low weight, while in the private school these results were, respectively, 66,66% and 80,49%. The results pointed the need of teachers and health professionals to work the self-acceptance of the body image, the self-esteem and the practice of healthy habits with this group of people whose body image and habits are so influenced by the media.
Keywords: Body image; adolescents; anthropometry.